2020
DOI: 10.1253/circj.cj-20-0306
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of Tissue Protrusion by Using Optical Coherence Tomography and Coronary Angioscopy Immediately After Stent Implantation

Abstract: necrotic core would be easily disrupted and can protrude between stent struts, resulting in an irregular protrusion. 6 However, irregular protrusion has not yet been validated by macroscopic pathology and histology. Coronary angioscopy (CAS) has allowed for the direct visualization of the intracoronary structure and provided substantial information pertaining to macroscopic pathology in living patients. 7 Therefore, the aim of the present study was to assess the relationship between the characteristics of tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Importantly, IP has been identified as an independent predictor of target lesion revascularization, underscoring its clinical relevance. 10 , 33 , 34 However, it must be recognized that despite the independent association between PPG and IP, the predicted capacity of PPG to detect IP was modest (area under the curve of 0.66). We also found that vessels with diffuse CAD (low PPG at baseline) had a higher prevalence of ISA after PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, IP has been identified as an independent predictor of target lesion revascularization, underscoring its clinical relevance. 10 , 33 , 34 However, it must be recognized that despite the independent association between PPG and IP, the predicted capacity of PPG to detect IP was modest (area under the curve of 0.66). We also found that vessels with diffuse CAD (low PPG at baseline) had a higher prevalence of ISA after PCI.…”
Section: Discussionmentioning
confidence: 99%
“…While prior IVUS research posits a contributory role for stent type and design in TP prediction, 34 several studies contradict, citing negligible variations in TP rates across diverse stent types and designs. 3 , 4 , 22 , 35 This study underscores that neither the metal composition nor the structural design of the stent is as critical as the inherent lesion morphology or the rigor of the implantation methodology.…”
Section: Discussionmentioning
confidence: 90%
“…Coronary angioscopies have revealed a correlation between OCT-identified TP post-stent deployment and the presence of advanced yellow plaque thrombotic activity. 22 , 23 Calcified nodules represent another prevalent plaque morphology within lesions accompanied by TPs. This study underscored a heightened incidence of calcified nodules within calcified TPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, combined OCT and angioscopic analysis for tissue protrusion revealed that yellow plaque was observed at a significantly higher rate in OCT-detected IP. 27 Fourth, it is often challenging to discriminate thrombus from protruding tissue, including IP, that is generated from a necrotic core using OCT. Previous research suggested a close association between thrombus and IP.…”
Section: Discussionmentioning
confidence: 99%